Evaluation of safety profile of the essential oils of eight Heracleum taxa (Apiaceae) related to determined furanocoumarin content - Ušjak Ljuboš; Drobac Milica; Niketić Marjan; Petrović Silvana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
For essential oils of roots, leaves, flowers and fruits of eight Heracleum taxa (H. sphondylium, H. sibiricum, H. montanum, H. ternatum, H. pyrenaicum subsp. pollinianum, H. pyrenaicum subsp. orsinii, H. verticillatum and H. orphanidis), we previously demonstrated antimicrobial, cytotoxic (selective to cancer cells) and/or antioxidant activities. In this work, for these essential oils maximum daily intake related to total furanocoumarins (FCs) content was estimated, according to Committee on Herbal Medicinal Products of European Medicines Agency (EMA/HMPC) recommendations. FCs were quantified using gas chromatography, and their sum equivalent to xanthotoxin (8-methoxypsoralen, 8-MOP) was calculated. It was shown that daily intake, not contributing significantly to overall risk (equivalent to intake of 1.5 mg FCs) for root essential oils was in the range of 1.94-5.23 mL, for fruit oils of 5.23-15.68 mL and for leaf or flower oils of 2.90-15.68 mL. Daily intake, not posing any unacceptable risk (equivalent to intake of 15 mg FCs) for root oils was in the range of 0.02-0.05 mL, for fruit oils of 0.05-0.16 mL and for leaf or flower oils of 0.03-0.16 mL. This work demonstrates the application of current EMA/HMPC recommendations, in order to establish safety profile of herbal preparations containing FCs.